Influence of exploitation conditions on anti-skid properties of tyres - Pokorski, Janusz; Sar, Hubert; Reński, Andrzej (Transport, 2019)
Tyre-to-road adhesion plays an important role when taking into account transmission of forces between tyres and road surface. It consequently influences vehicle safety. Moreover, it plays a significant role for modelling vehicle motion, which is often applied in the development of automotive active safety systems and in traffic accidents reconstruction. Furthermore, tyre-to-road adhesion properties are dependent on many factors. One of the factors is the type of tyre – summer or winter. This is the reason why it is justified to study the anti-slip properties of summer and winter tyres. This paper shows the method of measuring tyre-to-road adhesion coefficient. It is based on a skid resistance tester SRT-4 that consists of a special dynamometer trailer, towing vehicle and test-measuring equipment. It was designed to be applied in civil/road engineering and further developed. As a result, the SRT-4 system automatically obtains adhesion characteristics, such as the graph of tyre-to-road adhesion coefficient as a function of wheel slip ratio and velocity characteristics of lock-up adhesion coefficient. Results of the study present the above mentioned characteristics for different types of tyres (summer, winter) in different exploitation conditions. Differences between presented characteristics caused by tyre type and conditions of exploitation are shown. For example, for winter tyres we noticed that the peak value of adhesion coefficient was attained for higher values of slip ratio as compared with summer tyres.